Youth collective entrepreneurship based on the Social Economy as a tool for the prevention of violence - Macías de la Torre, Carolina; Reyes Cristóbal, Verenice (DIXI, 2020)
Objectives: The purpose of this article is to carry out an exercise to systematize the experience of implementing a program designed for the prevention of violence in youth in Mexico, from the perspective of the Social Economy. The program is implemented in various States of the Republic promoting collective undertakings with young people at risk, based on the accompaniment and incubation methodology of the Universidad Iberoamericana Puebla. The central axis of the project is the development of skills for young people to strengthen protective factors against this risk.Methodology: The objective and basic fundamentals of the project are described in this article, as well as its implementation in the different territories in Mexico, emphasizing the accompanying methodology used to incubate collective undertakings.Conclusions: It concludes by presenting the reference of some cases of accompanied collective undertakings and ends with some observations derived from the accompaniment that has been given to these groups in two years of work.
Keywords: construction of citizen security; youth collective entrepreneurship; youth at risk; ecological model for the prevention of violence; prevention of violence